Some Isolated Subsegmental Pulmonary Artery Defects Seen on Pulmonary CT Angiography May Not Represent True Pulmonary Embolism. Issue 2 (March 2016) - George, Jason; Lande, Leah
Abstract : Synopsis: Pulmonary computed tomographic angiography has overtaken all other diagnostic modalities to detect pulmonary embolism due to its high sensitivity, widespread availability, and rapid image acquisition. In some cases, isolated subsegmental defects are identified as pulmonary embolism. A fraction of these studies may be interpreted as negative when reviewed by expert thoracic radiologists, questioning the diagnostic accuracy of computed tomographic angiography for these small single defects. Furthermore, the clinical significance of these isolated subsegmental defects remains unclear. Source: Hutchinson BD, Navin P, Marom E, et al. Overdiagnosis of pulmonary embolism by pulmonary CT angiography. Am J Roentgenol . 2015;205:271–277.